Antiviral Treatment Alters the Frequency of Activating and Inhibitory Receptor-Expressing Natural Killer Cells in Chronic Hepatitis B Virus Infected Patients. (10th December 2012) - Lv, Juan; Jin, Qinglong; Sun, Haibo; Chi, Xiumei; Hu, Xiaoli; Yan, Hongqing; Pan, Yu; Xiao, Weihua; Tian, Zhigang; Hou, Jinlin; Xu, Damo; Tu, Zhengkun; et al.
Abstract : Natural killer (NK) cells play a critical role in innate antiviral immunity, but little is known about the impact of antiviral therapy on the frequency of NK cell subsets. To this aim, we performed this longitudinal study to examine the dynamic changes of the frequency of different subsets of NK cells in CHB patients after initiation of tenofovir or adefovir therapy. We found that NK cell numbers and subset distribution differ between CHB patients and normal subjects; furthermore, the association was found between ALT level and CD158b + NK cell in HBV patients. In tenofovir group, the frequency of NK cells increased during the treatment accompanied by downregulated expression of NKG2A and KIR2DL3. In adefovir group, NK cell numbers did not differ during the treatment, but also accompanied by downregulated expression of NKG2A and KIR2DL3. Our results demonstrate that treatment with tenofovir leads to viral load reduction, and correlated with NK cell frequencies in peripheral blood of chronic hepatitis B virus infection. In addition, treatments with both tenofovir and adefovir in chronic HBV infected patients induce a decrease of the frequency of inhibitory receptor + NK cells, which may account for the partial restoration of the function of NK cells in peripheral blood following treatment.